Non-traumatic testicular dislocation mimicking incarcerated inguinal hernia in a one-year-old boy - Naruki Higashidate; Suguru Fukahori; Shinji Ishii; Nobuyuki Saikusa; Naoki Hashizume; Yoshinori Koga; Daisuke Masui; Shiori Tsuruhisa; Takato Aikoh; Shoutarou Taki; Yoshiaki Tanaka; Minoru Yagi (Elsevier, 2018)
Testicular dislocation usually results from trauma to the scrotum or abdominoperineal area. We herein report a case of non-traumatic testicular dislocation in a one-year-old male patient. The patient was referred to our hospital due to intermittent irritability and a palpable mass with erythema at the left groin. The differential diagnosis was incarcerated inguinal hernia and testicular torsion. We could not discriminate the former from the later even with contrast-enhanced computed tomography, so we performed exploratory laparoscopy. Although patency of the processus vaginalis was found on the left side, protrusion of the intraabdominal organs was not found. The definitive diagnosis of testicular dislocation was made after the inguinal canal was opened via oblique incision at the left groin. The testis was excised because of complete necrosis, and orchidopexy on the contralateral testis was performed. Physicians should be aware of the possibility of testicular dislocation with a non-traumatic etiology. It is difficult to distinguish blood flow disturbance in an undescended testis from incarcerated inguinal hernia because of similarities in the findings of a clinical investigation. Exploratory laparoscopy is useful for making a definitive diagnosis and deciding on a surgical approach. Keywords: Testicular dislocation, Undescended testis, Orchiectomy, Incarcerated inguinal hernia